Rewilding with the beaver in Portugal: an economic analysis - Veríssimo, Daniel Alexandre Azevedo (2021)
Rivers and streams in Portugal are in poor ecological condition. River restoration programs are therefore seen as essential. It is well established that the beaver is an important tool for improving the ecological state of fresh water habitats. This study aims to determine the potential to use beavers has a tool in future river restoration programs. The work compares, from an economic and environmental perspective, an active management approach in the form of traditional river restoration actions and a passive management strategy in the form of beaver reintroduction. First, a brief overview of the conditions for the European beaver to return to the Portuguese landscape is presented. Second, an economic estimation based on the potential to save on habitat restoration costs, beaver management expenditures and the funds required for a reintroduction program is provided. These estimates are compared with the APA 2018-2020 river restoration program. Third and lastly, the likely large-scale landscape effects are analysed based on documented dynamics for the specie. The results indicate that the conditions exist for the beaver to return to Portugal. The benefits associated with the specie outweigh the costs and the landscape effects are broadly positive. The beaver, besides saving costs in river restoration programs, creates conditions for wildlife to thrive, delivers a wide range of ecosystem services and develops a landscape more resilient to climate change.